Sistem Informasi Hasil Perikanan Berbasis Jaringan Pada Dinas Kelautan Dan Perikanan Provinsi Lampung - Zaini, T M; Destasari, Layana (Jurnal Informatika, 2010)
Marine and Fisheries Department Lampung Province is a government institution has the duty of carrying out some of the government in the field of maritime affairs and fisheries based on the principle of autonomy, which is responsible for the deconcentration and assistance duty and other duties in accordance with the policies established by the Governor. Marine and Fishery Department purpose to develop monitoring and controlling the use of marine resources as well as supporting and coordinating human resource management of marine resources in coastal or provincial affairs. The system of fishery products in Lampung Province Department of Maritime affairs and Fisheries, not maximum. Based on the problems, the authors developed a system based fisheries information network at Marine and Fishery Department Lampung Province is fishery production and export of fishery production, which uses Microsoft Visual Basic 6.0 as programming language and Microsoft SQL Sever 2000 as the database. With network-based fisheries of information system at Marine and Fishery Department Lampung Province to help avoid errors and speed processing data efficiently and effectively in order to produce information quickly and accurately. Keyword : Fishery product, Information System